Work stress, fatigue and risk behaviors at the wheel: Data to assess the association between psychosocial work factors and risky driving on Bus Rapid Transit drivers (2017)
This Data in Brief (DiB) article presents a hierarchical multiple linear regression model that examine the associations between psychosocial work factors and risk behaviors at the wheel in Bus Rapid Transit (BRT) drivers (n1⁄4524). The data were collected using a structured self-administrable questionnaire made of measure- ments of wok stress (job strain and effort- reward imbalance), fatigue (need for recovery and chronic fatigue), psychological distress and demographics (professional driving experience, hours driven per day and days working per week). The data contains 4 parts: descriptive statistics, bivariate correlations between the study variables and a regression model predicting risk behaviors at the wheel and the entire study dataset. For further information, it is convenient to read the full article entitled “Stress-related Psychosocial Factors at Work, Fatigue, and Risky Driving Behavior in Bus Rapid Transport (BRT) Drivers”, published in Accident Analysis & Prevention.